2020
DOI: 10.1186/s13054-020-02951-1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma complications and in-hospital mortality: failure-to-rescue

Abstract: Background Reducing medical errors and minimizing complications have become the focus of quality improvement in medicine. Failure-to-rescue (FTR) is defined as death after a surgical complication, which is an institution-level surgical safety and quality metric that is an important variable affecting mortality rates in hospitals. This study aims to examine whether complication and FTR are different across low- and high-mortality hospitals for trauma care. Methods This was a retrospective cohort study performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 18 publications
6
39
3
Order By: Relevance
“…Although no incidents were recorded from high altitudes, as most of cases were from heights less than 10 meters, which we believe is a matter of the availability and adherence to safety measures at work and in or outdoor, the lack of training programs for fall prevention and work experience especially among construction workers. However, the mortality rate during or after treatment (1.2%) of the total significant trauma in line with the average reports of (1.18-3.7%) in-hospital mortality in other regions indicates an acceptable level of management in this hospital [24][25][26]. 2.…”
Section: Discussionsupporting
confidence: 77%
“…Although no incidents were recorded from high altitudes, as most of cases were from heights less than 10 meters, which we believe is a matter of the availability and adherence to safety measures at work and in or outdoor, the lack of training programs for fall prevention and work experience especially among construction workers. However, the mortality rate during or after treatment (1.2%) of the total significant trauma in line with the average reports of (1.18-3.7%) in-hospital mortality in other regions indicates an acceptable level of management in this hospital [24][25][26]. 2.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, as is the case for many retrospective databases, there is likely a significant issue of under-reporting in the data set. As such, a recent study from Japan, investigating 184 214 patients, reported a PTC rate of 12.8%, 21 as opposed to 2.8% in this study. Although obvious differences in number and definitions of reported PTC exist between data sets, the presented results should be interpreted in light of the underlying data set.…”
Section: Discussioncontrasting
confidence: 53%
“…In hospital settings, the failure to identify deteriorating patients can lead to delays in appropriate patient care [1][2][3], which can cause increased morbidity and mortality [4,5]. A recent qualitative study of surgical intensive care unit (ICU) nurses found that their ability to quickly identify deteriorating patients led to the early deployment of the rapid response team [6].…”
Section: Introductionmentioning
confidence: 99%